2015
DOI: 10.1371/journal.pone.0119966
|View full text |Cite
|
Sign up to set email alerts
|

Highly Heterogeneous Soil Bacterial Communities around Terra Nova Bay of Northern Victoria Land, Antarctica

Abstract: Given the diminished role of biotic interactions in soils of continental Antarctica, abiotic factors are believed to play a dominant role in structuring of microbial communities. However, many ice-free regions remain unexplored, and it is unclear which environmental gradients are primarily responsible for the variations among bacterial communities. In this study, we investigated the soil bacterial community around Terra Nova Bay of Victoria Land by pyrosequencing and determined which environmental variables go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 31 publications
(42 reference statements)
4
29
1
Order By: Relevance
“…For example, they predominate in the cinder deposits of the Kilauea volcano (38), in lava caves (25), in high-elevation mineral soils (20), in soil from CO 2 gas vents in the Calatrava volcanic field in Spain (29), in orthoquartzite caves in Venezuela (2), in the dark oligotrophic volcanic ice caves of Mt. Erebus in Antarctica (34), in soil from northern Victoria Land in Antarctica (17), and in geothermal soils on Pantelleria Island in Italy (12). Furthermore, most of the environments in which Ktedonobacteria have been found to predominate are acidic (2, 12, 17, 20, 29, 34); a survey of microbial ecosystems in the soil of Antarctica showed that they markedly decreased with increases in pH in the range of pH 5 to 7 (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, they predominate in the cinder deposits of the Kilauea volcano (38), in lava caves (25), in high-elevation mineral soils (20), in soil from CO 2 gas vents in the Calatrava volcanic field in Spain (29), in orthoquartzite caves in Venezuela (2), in the dark oligotrophic volcanic ice caves of Mt. Erebus in Antarctica (34), in soil from northern Victoria Land in Antarctica (17), and in geothermal soils on Pantelleria Island in Italy (12). Furthermore, most of the environments in which Ktedonobacteria have been found to predominate are acidic (2, 12, 17, 20, 29, 34); a survey of microbial ecosystems in the soil of Antarctica showed that they markedly decreased with increases in pH in the range of pH 5 to 7 (17).…”
Section: Discussionmentioning
confidence: 99%
“…Erebus in Antarctica (34), in soil from northern Victoria Land in Antarctica (17), and in geothermal soils on Pantelleria Island in Italy (12). Furthermore, most of the environments in which Ktedonobacteria have been found to predominate are acidic (2, 12, 17, 20, 29, 34); a survey of microbial ecosystems in the soil of Antarctica showed that they markedly decreased with increases in pH in the range of pH 5 to 7 (17). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high abundance of Actinobacteria is in stark contrast to Arctic and other Antarctic sites commonly dominated by Proteobacteria, Cyanobacteria, and Acidobacteria (Steven et al, 2007, 2013; Koyama et al, 2014). For example, the McMurdo Dry Valleys, a well-studied site of Antarctica, has been found to be dominated by Proteobacteria (Clocksin et al, 2007; Cary et al, 2010); Miers Valley, is dominated by Bacteriodetes, Proteobacteria, and Actinobacteria (Stomeo et al, 2012), and Victoria Land is comprised of a heterogeneous bacterial community encompassing Proteobacteria, Acidobacteria, Actinobacteria, Chloroflexi, and Cyanobacteria (Kim et al, 2015). The variability in diversity structures in each of these sites may be due to variable organic matter content (Takebayashi et al, 2007; Bell et al, 2013; Ji et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Using publicly available data (Curtosi et al 2010;Guerra et al 2011;Lee et al 2012;Laluraj et al 2014;Vodopivez et al 2014;Grotti et al 2015;Kim et al 2015), we compared the concentrations of eight heavy metals (As, Cd, Co, Cr, Cu, Hg, Ni, and Zn) in 15 samples originating from different Antarctic regions (including five soil samples, eight marine/surface sediments samples and two snow/ice samples). Seven samples originated from King George Island.…”
Section: Chemical Characterization Of the Sampling Sitesmentioning
confidence: 99%